Surfactant biodegradation - Danial, Wan Hazman (Springer Nature, 2022)
Although surfactants are being used extensively in detergents, food, pharmaceuticals, and cosmetics and in industries and various other sectors due to their diverse functions, they also play a critical role in environmental contamination. For this reason, efforts must be made to address the biodegradation of surfactants in the environment. This chapter presents an overview of the degradation of surfactants and discusses in detail the impact of surfactants on the environment and the types and mechanisms of surfactant biodegradation. The factors influencing the biodegradation of surfactants are briefly discussed, while an assessment of the biodegradability of surfactants is also presented.